Effects of meloxicam administration on physiological and performance responses of transported feeder cattle - Guarnieri Filho, Thomaz Antonio [UNESP]; Cooke, R. F.; Cappellozza, B. I.; Reis, M. M.; Marques, R. S.; Bohnert, D. W. (Amer Soc Animal Science, 2014)
This experiment evaluated the effects of meloxicam administration on physiological and performance responses of transported cattle during feedlot receiving. Eighty-four Angus x Hereford steers were ranked by BW on d -10 and assigned to 21 dry lot pens. From d -10 to 0, pens were fed alfalfa-grass hay ad libitum and 2.4 kg/steer daily (DM basis) of a corn-based concentrate. On d 0, pens were randomly assigned to 1) transport for 1,440 km in a livestock trailer and oral administration of meloxicam (1 mg/kg of BW) at loading (d 0), unloading (d 1), and daily from d 2 to 7 of feedlot receiving (MEL; n = 7); 2) the same transportation and treatment schedule of MEL but oral administration of lactose monohydrate (1 mg/kg of BW) instead of meloxicam (TRANS; n = 7); or 3) no transport and oral administration of lactose monohydrate (1 mg/kg of BW) concurrently with treatment administration to MEL and TRANS (CON; n = 7). Upon arrival (d 1), MEL and TRANS steers returned to their pens for a 21-d feedlot receiving with the same diet offered from d -10 to 0. Treatments were administered to steers via oral drench on d 0 and 1 or mixed daily with the concentrate from d 2 to 7. Full BW was recorded before (d -2, -1, and 0) treatment application and at the end of experiment (d 20, 21, and 22) for ADG calculation. Daily DMI was recorded from d 1 to 21. Blood samples were collected on d 0, 1, 3, 5, 7, 10, 14, and 21. During the initial 7 d of feedlot receiving, hay and total DMI were reduced (P <= 0.03) in TRANS vs. CON and MEL and similar between CON and MEL (P >= 0.26), whereas concentrate DMI did not differ (P = 0.16) among treatments. Mean ADG was reduced (P <= 0.03) in TRANS vs. MEL and CON but similar (P = 0.82) between MEL and CON. Moreover, TRANS had reduced G: F vs. CON (P = 0.01) and MEL (P = 0.05), whereas G:F was similar (P = 0.39) between CON and MEL. Serum NEFA concentrations were greater (P < 0.01) for TRANS and MEL vs. CON on d 1. Plasma haptoglobin concentrations were greater (P = 0.03) for TRANS vs. CON and MEL on d 5 and greater (P = 0.03) for CON vs. TRANS on d 10. Plasma ceruloplasmin concentrations were greater (P <= 0.04) for TRANS vs. CON on d 3, 5, 7, 10, and 14, greater (P = 0.03) for TRANS vs. MEL on d 5 and 7, and also greater (P = 0.05) for MEL vs. CON on d 3. In conclusion, meloxicam administration to feeder steers modulated the haptoglobin and ceruloplasmin responses and prevented the performance losses caused by long-distance transportation.
Keywords: acute-phase proteins; beef cattle; feedlot receiving; meloxicam; transport